3H activity comparison between FTMC, VNIIM and LNE-LNHB. (March 2016) - Cassette, Philippe; Butkus, Paulius; Gudelis, Arunas; Shilnikova, Tatiana
Abstract: An activity comparison of tritiated water was organized in 2013 between 3 laboratories: FTMC (Lithuania), LNE-LNHB (France) and VNIIM (Russia). The solution was prepared by LNHB and ampoules were sent to the others laboratories. This solution was standardized in terms of activity per unit mass by participant laboratories using the Triple to Double Coincidence Ratio (TDCR) method in liquid scintillation counting (LSC). The tritiated water solution is traceable to the solution prepared by LNHB for the CCRI(II)-K2.H-3 2009 3 H international comparison. Highlights: International comparison of the activity concentration of tritiated water. All laboratories used the Triple to Double Coincidence Ratio method in Liquid Scintillation. Instruments, methods and uncertainty budgets are detailed. The reported results are compatible within the uncertainties but significant differences in the uncertainty evaluation is reported.